Sub-picosecond C=C bond photo-isomerization: evidence for the role of excited state mixing - Agathangelou, Damianos; Roy, Partha Pratim; Marin, Maria del Carmen; Ferré, Nicolas; Olivucci, Massimo; Buckup, Tiago; Léonard, Jérémie; Haacke, Stefan (Comptes rendus physique, 2021)
Sub-picosecond photo-isomerization is the major primary process of energy conversion in retinal proteins and has as such been in the focus of extensive theoretical and experimental work over the past decades. In this review article, we revisit the long-standing question as to how the protein tunes the isomerization speed and quantum yield. We focus on our recent contributions to this field, which underscore the concept of a delicate mixing of reactive and non-reactive excited states, as a result of steric properties and electrostatic interactions with the protein environment. Further avenues and new approaches are outlined which hold promise for advancing our understanding of these intimately coupled chromophore-protein systems.
Gesehen am 29.07.2022